2013
DOI: 10.1371/journal.pone.0073273
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, High-Molecular-Weight (HMW) Adiponectin, and Metabolic Risk Factors: Prevalence and Gender-Specific Associations in Estonia

Abstract: BackgroundThe metabolic consequences of obesity are associated with an imbalance of adipocytokines, e.g. adiponectin. However, some obese subjects remain metabolically healthy and have adiponectin levels similar to normal body weight subjects. Current estimates of the prevalence of obesity in Estonia have relied only on self-report data.ObjectivesTo estimate the prevalence of obesity in Estonia, to test for associations between HMW adiponectin and metabolic risk factors and to test if HMW adiponectin levels di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…This suggests that blood adiponectin levels could serve as a potential biomarker for cardiometabolic risk in MUNW, MHO, and MUO individuals that is independent of body weight. This is further supported by another study showing that adiponectin was positively correlated with HDL-c and inversely associated with TG levels, adiposity parameters, insulin resistance, and blood glucose (67).…”
Section: Cytokines and Adipokinessupporting
confidence: 69%
“…This suggests that blood adiponectin levels could serve as a potential biomarker for cardiometabolic risk in MUNW, MHO, and MUO individuals that is independent of body weight. This is further supported by another study showing that adiponectin was positively correlated with HDL-c and inversely associated with TG levels, adiposity parameters, insulin resistance, and blood glucose (67).…”
Section: Cytokines and Adipokinessupporting
confidence: 69%
“…From the 27 selected articles, the MHO prevalence was defined as an objective in 14 studies (52%) (11,14,15,17,20,21,23,(25)(26)(27)29,30,34,35).…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
“…The target population was described in four studies (15%) (16,17,24,27). The probability sampling was described in 19 studies (70%) (8,9,(13)(14)(15)(17)(18)(19)(20)(21)(22)(26)(27)(28)(29)31,(33)(34)(35). Nine studies (33%) described the response rate, and of these only four (13,15,16,21) reported rates 786 Prevalence of metabolically healthy obesity J. P. Rey-López et al obesity reviews ≥70%.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-obese and obese women, serum RBP-4 was highest among those with visceral adiposity as compared to those without, and levels were not different between the non-obese and obese groups that did not have visceral adiposity (265). MHO individuals also have higher circulating levels of high-molecular weight (HMW) adiponectin (9, 103, 107) and lower FFA (340, 482) as compared to insulin resistant obese individuals. These factors may contribute to the protection from metabolic dysfunction in MHO despite having excess adiposity.…”
Section: Adiposity and Insulin Resistancementioning
confidence: 99%